Model Management Training Based on Addie To Improve School Librarians’ Competence in Achieving Excellent Library Accreditation - Ibnu Hajar; Yuniarto Mudjisusatyo; Saut Purba (Graduate Program Magister Manajemen Pendidikan, 2026)
Purpose of the study: This study aims to develop and evaluate an ADDIE-based training management model to improve school librarians’ competencies in supporting the achievement of excellent library accreditation standards in senior high schools in Binjai City. Methodology: This study employed a Research and Development (R&D) methodology based on the ADDIE model. Data collection techniques comprised interviews, observations, expert validation instruments, and competency assessments. The data were analyzed statistically using the Shapiro–Wilk test for normality, paired sample t-test, and N-Gain score analysis with the assistance of SPSS software. Main Findings: The developed model was validated as feasible by experts and demonstrated significant effectiveness. Pretest and posttest scores increased substantially in both limited and large group trials. Statistical testing confirmed significant differences, and N-Gain results indicated high effectiveness categories. Applications of this study: The training model can be applied in educational institutions, school systems, and librarian professional development programs. It is particularly useful for schools preparing library accreditation and for education authorities seeking structured competency improvement strategies. Novelty/Originality of this study: This study provides an empirically tested ADDIE-based training management model specifically designed for school librarians and linked to accreditation standards. The research integrates instructional design theory, professional competency development, and accreditation requirements within a single framework.